A Pseudospectral Method for Solving Navier-Stokes Equations (Journal of Computational Mathematics, 1991)
In this paper, we propose a new kind of pseudospectral schemes with a restraint operator to solve the periodic problem of Navier-Stokes equations. The generalized stability of the schemes is analysed and convergence is proved. Numerical results are presented also.